Pengaruh Kualitas Pelayanan dan Komunikasi terhadap Kinerja Karyawan di PT Stars Yudhatama Indonesia - Jayadi, Rahmat; Madiistriyatno, Harries; Taufik, Kemal (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study analyzes the effect of service quality and communication on employee performance at PT. Stars Yudhatama Indonesia. Using a quantitative descriptive design with a sample of 69 respondents from a population of 218 employees, this study found that service quality and communication have a positive and significant effect on employee performance. The results of the validity and reliability tests show that the research instrument meets methodological standards. Correlation and regression analysis show that service quality contributes 78.8% and communication 82.1%, while simultaneously both contribute 89.7% to employee performance. The regression equation Y = 6.406 + 0.459X₁ + 0.661X₂ indicates that communication has a more dominant influence than service quality. These findings provide an empirical basis for developing strategies to improve employee performance through optimizing service quality and improving communication patterns in the context of digital transformation of work processes and human resource management.